The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biomedicines10102462
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin as a Potential Marker of Resolution of Inflammation in COVID-19 Infection

Abstract: Chemerin is one of the specialized pro-resolving mediators that participate in the early phase of inflammation and contribute to the initiation of the pro-resolving response. There is a paucity of data regarding the time course of chemerin during acute infections. We aimed to evaluate the sequence of inflammatory responses in the acute COVID-19 phase throughout onset and resolution of inflammation. We evaluated changes in selected biomarkers in COVID-19 survivors on the 7-day and 28-day follow up. Chemerin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
4
11
0
1
Order By: Relevance
“…Furthermore, higher PTX3 plasma levels were found in 14 patients with subsequent thrombotic complications [ 36 ]. Sulicka-Grodzicka et al, in a manner consistent with previous work, found higher levels of PTX3 in severe COVID-19 patients than in non-severe COVID-19 [ 38 ]. The authors evaluated the sequence of inflammatory responses in acute COVID-19 through a 28-day follow-up, discovering that the resolution of inflammation in the group of moderate/severe SARS-CoV2 infection was associated with decreasing PTX3 serum concentrations [ 38 ].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, higher PTX3 plasma levels were found in 14 patients with subsequent thrombotic complications [ 36 ]. Sulicka-Grodzicka et al, in a manner consistent with previous work, found higher levels of PTX3 in severe COVID-19 patients than in non-severe COVID-19 [ 38 ]. The authors evaluated the sequence of inflammatory responses in acute COVID-19 through a 28-day follow-up, discovering that the resolution of inflammation in the group of moderate/severe SARS-CoV2 infection was associated with decreasing PTX3 serum concentrations [ 38 ].…”
Section: Resultssupporting
confidence: 82%
“…Sulicka-Grodzicka et al, in a manner consistent with previous work, found higher levels of PTX3 in severe COVID-19 patients than in non-severe COVID-19 [ 38 ]. The authors evaluated the sequence of inflammatory responses in acute COVID-19 through a 28-day follow-up, discovering that the resolution of inflammation in the group of moderate/severe SARS-CoV2 infection was associated with decreasing PTX3 serum concentrations [ 38 ]. The authors performed a time course analysis of PTX3 on day 1, day 7, and day 28 after infection [ 38 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In patients with moderate or severe acute infection, serum chemerin levels first decreased on Day 7 in comparison to the day of hospital admission and subsequently increased at the 28-day follow-up. As this profile of plasma chemerin levels was not observed in COVID-19 patients with mild disease over this 28-day period, it was suggested that serum chemerin levels are considered as a marker for the resolution of inflammation [63]. However, while randomized clinical trials proved that anti-inflammatory and pro-resolving corticosteroids can improve survival in severe COVID-19 [64], dexamethasone therapy did not affect plasma chemerin levels [62].…”
Section: Chemerinmentioning
confidence: 84%